Risk Factors for Fatal Pulmonary Hemorrhage following Concurrent Chemoradiotherapy in Stage 3B/C Squamous-Cell Lung Carcinoma Patients - Topkan, Erkan (J Oncol, 2018)
We aimed to identify the fatal pulmonary hemorrhage- (FPH-) related risk factors in stage 3B/C squamous-cell lung carcinoma (SqCLC) patients treated with definitive concurrent chemoradiotherapy (C-CRT). Medical records of 505 stage 3B/C SqCLC patients who underwent 66 Gy radiotherapy plus 1-3 cycles of concurrent chemotherapy with available pretreatment thoracic computerized tomography scans were retrospectively analyzed. Primary end-point was the identification of FPH-related risk factors. Examined factors included the basal patient and tumor characteristics with specific emphasis on the tumor cavitation (TC) status, tumor size (TS) and cavitation size (CS), tumor volume and cavitation volume (TV and CV), relative cavitation size (RCS = CS/TS), and relative cavitation volume (RCV=CV/TV). FPH emerged in 13 (2.6%) patients, with 12 (92.3%) of them being diagnosed ≤12 months of C-CRT. All FPHs were diagnosed in patients with TC (N=60): group-specific FPH incidence: 21.6%. TC (P<0.001) was the unique independent factor associated with higher FPH risk in multivariate analysis. Further analysis limited to TC patients exhibited the RCV>0.14 (37.5% versus 11.1% for RCV≤0.14; P<0.001), major RCS group [31.0% versus 19.0% for minor versus 0% for minimum RCS; P=0.008), and baseline hemoptysis (26.3% versus 13.6% for no hemoptysis; P=0.009) as the independent risk factors for higher FPH incidence. FPH was an infrequent (2.6%) complication of C-CRT in stage 3B/C SqCLC patients, but its incidence increased to 37.5% in patients presenting with TC and RCV>0.14. Diagnosis of >90% FPHs ≤12 months of C-CRT stresses the importance of close and careful follow-up of high-risk patients after C-CRT for multidisciplinary discussion of possible invasive preventive measures.